Observation of coliform bacteria in five coastal along Kelantan - Mariam Firdhaus Mad Nordin; Marinah Muhammad; Nurul' Ain Abdullah (2011)
The observation of coliform bacterial counts along Kelantan coasts was studied on July and September 2011. Samples of coastal water were collected at five sampling station along Kelantan coasts, the selection of beaches bases on popularity,population density and suggested by Department of Environment (DOE). The samples analyzed using multiple-tube fermentation technique as described in 21st edition of Standard Method for Examination Water and Wastewater. Irama beach shows high of colofirm bacterial counts, 377 MPN/100 mL. However Sri Tujuh beach shows lower coliform bacteria count, 4 MPN/100 mL. The results obtain were compared with Malaysia interim Marine Water Quality Standard (IMWQS). Coastal water with coliform bacteria counts more than acceptable limit consider unsafe for shell fishing and swimming activity